Going to the potty - Rogers, Fred.; Judkis, Jim (New York : Putnam, 1986)
Parent and child may read together about the way children develop in the experience of eliminating waste products from their body and about the positive aspects of using the toilet.
Keywords: Toilet training -- Juvenile literature; Toilet training; Children -- Care and hygiene